A Universal Martial Tactic: The Shoulder Throw & Its Variations, by Allen Pittman (Revista de Artes Marciales Asiáticas, 2012)
Development of the fighting arts begins with universal principles found in human anatomy. As a result, in every culture we find combative techniques that share common tactics and applications. Additionally, many techniques travel across cultures. To illustrate just one martial tactic and its worldwide presence among martial traditions, this article presents variations on the shoulder throw as found in Persia, Greece, Japan, China, England, and France. Two main methods are found in the shoulder throw where the defender moves either inside or outside the attacker’s leading arm. The technical variations seem endless, as the defender can not only throw an opponent, but also employ joint locks, breaks, and even weapons in the techniques. An academic understanding, and/or the practical learning, of trans-cultural techniques, brings greater understanding of martial arts in general and a practical component to those who learn the skills for practical application.